PERAN MAJELIS DZIKIR DAN SHOLAWAT DALAM MENUMBUHKAH MOTIVASI KECINTAAN SANTRI TERHADAP SHOLAWAT - Muhammada Alwi Baharudin Habib; Sayidah Afyatul Masruroh; Robiah Machtumah Malayati; Fajar M Husen Husen; Robi Al Buchori Buchori (Menara Tebuireng, 2022)
The focus of this research is to examine the role of the Jamansiro Dzikir and Sholawat Assembly in increasing the motivation of the Santri's Love for Sholawat and how the Impact of the Jamansiro Dzikir and Sholawat Assembly is in Improving the Spirituality of the Santri. This research is a case study research. The approach used in this research is a naturalistic approach. The technique used in entering the location in conducting this research is to use formal and informal roads, the data sources used consist of Person, Place, and paper data. Data collection techniques using observation, interview, and documentation methods were carried out directly and supported by in-depth interviews with related parties.The conclusions of this study are: 1) The role of the Jamansiro Dzikir and Sholawat Assembly in increasing the motivation of the Santri's Love for Sholawat. The Jamansiro Dzikir and Sholawat Assembly has a very strategic role in increasing the spirituality of the santri because implicitly the activities of the Jamansiro Assembly have several functions, including: as a medium for implementing the principles of the Five Servants, as a medium for presenting exemplary figures in students, namely the figures of Rasulullah and Auliya', as a medium for cultivating mahabbah and self-motivation of students. as a medium to foster hope of obtaining ridlo and blessings from Allah through the reason (wasilah) of reading blessings and manaqib. 2). The Impact of the Dhikr Assembly and the Jamansiro Prayer in Improving the Spirituality of the Santri. The activities of the Jamansiro Assembly play a very important role in increasing the spirituality of the santri. Forms of spiritual improvement for students who actively take part in activities at the Jamansiro Assembly are: a high spirit of devotion, an attitude of tawadlu' and better morals. roja, and motivation to istiqomah.